Antinociceptive and anti-arthritic properties of hydroethanolic leaf extract of Clausena anisata (Willd.) Hook. f. ex Benth (Rutaceae) in Rodents: possible mechanism of actions (Nigerian Journal of Physiological Sciences, 2021)
Summary: The leaves of Clausena anisata (Willd.) Hook. f. ex Benth (Rutaceae) is used in Traditional African medicine for the treatment of various ailments including arthritis. The present study sought to investigate the antinociceptive and anti-arthritic properties of hydroethanolic leaf extract of Clausena anisata (HeCA). HeCA (100, 200 or 400 mg/kg, p.o.) was administered 1 h before intraplantar injection of formalin 1%v/v in saline to evaluate antinociceptive effect. Moreover, its possible mechanism of antinociceptive action was investigated through pretreatment of mice with antagonists of receptors implicated in nociception. Anti¬inflammatory effect of the extract was investigated using the carrageenan-induced paw oedema and complete Freund's adjuvant (CFA)-induced arthritis models in rats. HeCA (400 mg/kg) treatment significantly reduced the duration of paw licking/biting during both in the early (42.12%) and late (75.79%) phases of formalin-induced nociception. However, the antinociceptive effect elicited by HeCA was reverse by pretreatment of mice with naloxone, prazosin, yohimbine, ketanserin, L-arginine, and parachlorophenylalanine (PCPA). HeCA produced dose-dependent and time course decrease in carrageenan-induced paw oedema. Pre- and post-treatment of rats with HeCA ameliorated CFA-induced arthritis evidenced in the significant decrease in arthritic index comparatively similar to the effect of celecoxib. CFA- induced oxidative and nitrosative stress were attenuated by subchronic treatment with HeCA. Findings from this study shows that C. anisata possesses antinociceptive activity through possible interaction with opioidergic, noradrenergic, L-arginine-nitric oxide and serotonergic pathways as well as anti-arthritic property which could be attributed to its ability to prevent the release of inflammatory mediators and oxidative stress.
Keywords: Complete Freund's adjuvant; L-arginine-nitric oxide; nociception; antioxidant; rheumatoid arthritis; serotonergic